The Exile Based on a Novel by Oscar Micheaux - Heywood, Donald (BFI, 2016)
"The Exile" is the first sound feature made by an African-American and a remake of his own silent film, which was itself the first feature made at all by an African-American. The film fits well inside Micheaux's typical form of rangy melodrama - this time, perhaps literally, as it finds its protagonist, Jean Baptiste, fleeing the carnal heart of Chicago for the wide open ranges of a ranch in South Dakota. Here the film's author includes a piece of his own biography, having been a cattleman in South Dakota - an experience previously incorporated into his novel and an earlier film, both titled "The Homesteader" - and makes himself the hero. The film is framed by de facto black self-reliance, ignoring a culture that was willfully, violently suppressing black progress. Still, like other Micheaux films, "The Exile" does not shy away from depicting disrepair amongst the black population - it is as bold in its depiction of blacks murdering other blacks as it is unafraid of showing an empowered upper class of African-Americans partaking freely of the opportunities innate to our country. [www.zekefilm.org]